Novel Trocar-Free Elastic Liver Retractor in Bariatric Surgery Patients: Comparison of a Standard Laparoscopic Retraction With the First Series Using the LiVac Sling System. (April 2020) - Bures, Claudia; Seika, Philippa; Fiorelli, Rossano Alvim Keppler; Kröll, Dino; Zorron, Ricardo
During upper gastrointestinal surgery, retraction of the liver plays an essential role in the visualization and creation of an optimal surgical field. Liver retraction may be problematic, particularly in obese patients. The use of conventional liver retractors requires additional skin incision and has the potential to cause pain as well as liver injuries. The present study is the first to evaluate the performance and safety of the LiVac Sling (Livac Pty Ltd, Melbourne, Australia) trocar-free retractor system in bariatric surgery patients. In this retrospective study, data from laparoscopic primary or revisional bariatric surgeries that were performed with the LiVac Sling system and a standard retractor between May 2017 and December 2017 were collected. Demographic data, body mass index, type of surgery, number and indication of LiVac Sling system used, surgery time, and complications were analyzed. In total, 51 procedures were included. Twenty Sling devices have been used in 17 patients (13 female; 75%). The distribution of baseline characteristics was similar between the standard retractor group and LiVac Sling retractor group. In the LiVac Sling group, the number of trocars used was significantly reduced over the study period. Within 30 days postoperatively, no complications could be identified, and no device-related adverse events were reported. In this bariatric population, the use of the LiVac Sling for liver retraction was safe. No device-related adverse events were registered, and compared with standard retraction, the number of trocars used could be reduced by one.